A step into pharmacy : Faculty of Pharmacy UiTM Bertam visit to Sekolah Menengah Sains Kubang Pasu - Ibrahim, Nurul Alyaa; Karuppannan, Mahmathi (Faculty of Pharmacy, 2026)
On 7 February 2026, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Bertam Campus, was honoured to participate in an academic outreach programme at Sekolah Menengah Sains Kubang Pasu, Kedah. The visit marked UiTM Pulau Pinang’s first engagement with the school, following an invitation from the Parents and Teachers Association to introduce the academic programmes available at UiTM. The Faculty of Pharmacy was delighted to take part in this meaningful initiative by introducing the field of pharmacy to secondary school students and parents, while providing early exposure to educational opportunities in the healthcare sciences.